Pengaruh Current Ratio dan Debt to Equity Ratio Terhadap Kinerja Keuangan Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2023 - Nahlia, Nada; Rahmawati, Iroh (Media Akuntansi Perpajakan, 2025)
In assessing a company's financial performance, financial ratios serve as very important analytical instruments. Two ratios commonly used are the Curent Ration (CR) and Debt Equity Ratio  (DER). The CR measures the company's ability to meet its short-term obligations. A high CR value reflects good liquidity, but if it is too large, it may indicate that current assets are not being utilized productively. Conversely, the DER illustrates the company’s capital structure. A high DER signifies heavy reliance on debt financing, thereby increasing the financial risk faced by the company. This study aims to analyze the influence of CR and DER on financial performance, both partially and simultaneously, in mining subsector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. This research employs a quantitative approach with a sample of 13 mining subsector companies, resulting in 65 data observations. Data analysis was conducted with the assistance of the SPSS application. The test results indicate that CR and DER simultaneously have a significant positive effect on the company’s financial performance. Partial tests also show that each variable, both CR and DER, individually has a significant positive effect on financial performance. This study emphasizes the actual conditions of the mining subsector in Indonesia, which faces performance fluctuations as a result of changes in global commodity prices. The findings are expected to contribute to company management, investors, and regulators in understanding the role of CR and DER as important indicators in maintaining the stability and sustainability of the company’s financial performance